Komparasi Criteria Splitting Pada Algoritma Iterative Dichotomizer 3(ID3) Untuk Klasifikasi Kelayakan Kredit - Nandya Ayu Fatmandini; Rizal Amegia Saputra; Resti Yulistria (Paradigma, 2020)
Credit is a form of business run by various banks. In running credit, banks will always consider the credit that will occur, for that data about creditworthiness decisions will be very necessary to support the business wheels of banking life. Credit analysis is carried out to support credit or historical data. This can reduce credit. Bank Sinarmas Sukabumi is one of the largest finance companies in Indonesia. This company provides financing services for the purchase of new vehicles or used vehicles, some funds and funds provided by Sinarmas Bank in terms of credit, credit assistance, one for analyzing important credit, because one of them, looking for credit, bad things that can be done by companies that are not careful in granting credit. The ID3 algorithm can search all discussions and decisions. The application of the ID3 method by comparing the three criteria for obtaining credit, understanding the assessment criteria, obtaining an accuracy value of 62.67% and an AUC value of 0.800, the highest in accordance with the criteria being compared, is discussed with the criteria. The Strengthening Ratio and Gini Index have the lowest Accuracy and AUC values. Thus, the ID3 method with Gain Information criteria is a good method and criterion in predicting lending to Bank Sinarmas Sukabumi.